AmeÌrique septentrionale : PublieÌe sous les auspices de Monseigneur le duc d'Orleans [Sheet 1]. - Anville, Jean Baptiste Bourguignon d', 1697-1782 (chez l'auteur, aux Galeries du Louvre, 1746)
Map shows the geography, settlements, and Native American habitation in mid-eighteenth century North America that spans a majority of the the continent from the eastern coast to the Rio Grande region of "Nouveau Mexique." Inset: [Baffin Bay, Hudson Bay, Labrador, and Greenland]. Scale undetermined.